Towards a harmonisation of the soil map of Africa at the continental scale - Dewitte, Olivier; Jones, Arwyn; Spaargaren, Otto; Breuning-Madsen, Henrik; Brossard, Michel; Dampha, Almami; Deckers, Jozef; Gallali, Tahar; Hallett, Stephen H.; Jones, Robert J. A.; Kilasara, Method; LeRoux, Pieter; et al. (Elsevier, 2013)
In the context of major global environmental challenges such as food security, climate change, fresh water scarcity and biodiversity loss, the protection and the sustainable management of soil resources in Africa are of paramount importance. To raise the awareness of the general public, stakeholders, policy makers and the science community to the importance of soil in Africa, the Joint Research Centre of the European Commission has produced the Soil Atlas of Africa. To that end, a new harmonised soil map at the continental scale has been produced. The steps of the construction of the new area-class map are presented, the basic information being derived from the Harmonized World Soil Database (HWSD). We show how the original data were updated and modified according to the World Reference Base for Soil Resources classification system. The corrections concerned boundary issues, areas with no information, soil patterns, river and drainage networks, and dynamic features such as sand dunes, water bodies and coastlines. In comparison to the initial map derived from HWSD, the new map represents a correction of 13% of the soil data for the continent. The map is available for downloading.
Keywords: Soil map; Harmonisation; Soil classification; Soil Atlas of Africa; Google Earth